An Investigation of the Effects of Group Work Dynamics on Iranian Male and Female EFL Learners’ Motivation in Communicative Tasks - Farshood, Arya; Aghajanzadeh Kiasi, Behzad; Siahpoosh, Hosein; Taghipour Bazargani, Davood (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to examine the effects of group work dynamics (GWDs) on the motivation of Iranian male and female EFL learners during communicative tasks. This mixed-methods research was conducted with 80 intermediate-level Iranian EFL learners randomly assigned to experimental and control groups. Each group comprised 20 male and 20 female participants. All participants completed a pretest and a posttest assessing speaking performance and motivation. The experimental group received structured group work interventions over 20 sessions featuring communicative tasks such as object assembly, information gap activities, and comic strip storytelling. In contrast, the control group completed the same tasks individually without collaborative strategies. Participants’ interactions were video-recorded for observation, and ten learners were randomly selected for semi-structured interviews. Quantitative data were analyzed using SPSS to conduct descriptive and inferential statistical analyses, including t-tests and ANOVA. Qualitative data from observations and interviews were thematically coded and analyzed to evaluate the complexity and effectiveness of group dynamics. Results revealed that learners in the experimental group showed a statistically significant increase in motivation (M = 4.0138 posttest) compared to the control group (M = 3.5038 posttest), with the difference confirmed by a paired samples t-test (p ≤ .05). Gender-based analysis showed that while male learners experienced a greater gain in motivation (1.036-point increase), female learners had higher absolute motivation scores at both pretest and posttest stages. ANOVA results confirmed significant posttest differences among the four subgroups (male/female, control/experimental), indicating the intervention’s overall impact. Observational data revealed differing gender-based interaction patterns, with males exhibiting competitiveness and females demonstrating collaborative support. Interview responses confirmed that positive group energy and peer support enhanced learner engagement and sustained motivation throughout the program. Group work dynamics significantly improve EFL learners’ motivation when implemented effectively. While both genders benefit, the nature of their interaction influences the quality and style of motivation enhancement.